Cartoons for Young Learners: Pedagogical and Cultural Views - Zuraida Supri, Ida; Muammar Shidiq, Ilham; Nadira Awwali, Jasmine (International Journal of Psychosocial Rehabilitation, 2020)
Children generally love animated cartoons. An animated cartoon is a film that uses animation techniques to photograph a sequence of drawings rather than real people or objects. Stories in cartoons for children are humorous, yet they may deliver life principles and concepts. Besides having a good time enjoying the cartoons, children learn and understand other people’s habits or cultures. As an addition, children can be exposed to English pronunciation, intonation, and stress in spoken English. Charlie and Lola is a cartoon produced by the BBC about a sibling’s daily life. Charlie is a caring brother, and Lola is a witty, cute sister. The stories are depicted in a simple yet interesting way. Showing this to young learners’ class is expected to lead to better intercultural understanding, broaden their knowledge, and make sense of the world. McCloseky and Thornton (2002) propose that using stories (in cartoons) is very appealing and makes teaching more effective. Deacon and Murphy (2001) also add that stories also introduce new vocabulary and language forms within rich networks of associations. Therefore, integrating stories, specifically cartoons, in teaching and learning English may enhance young learners’ English and other related aspects even more as it is done deliberately this way. This paper will report on 1) young learners’ learning characteristics attended by Charlie and Lola Cartoon 2) language and cultural points they learn, and 3) their responses to the cartoon.